Whether Chinese Medicine Have Effect on Halitosis: A Systematic Review and Meta-Analysis. (26th November 2018) - Wu, Xinyu; Zhang, Jie; Zhou, Yikun; He, Ze; Cai, Qiaoyi; Nie, Min
Abstract : Object . Halitosis has great adverse impact on personal and social life. There is no strong evidence for the effect of Chinese medicine (CM) and combined Chinese and western medicine (CWM) on halitosis. The aim of the present study is to evaluate the effective rate of CM and CWM on halitosis. Materials and Methods . Literature search in English and Chinese was conducted in PubMed, Embase, CNKI, CBM, and Wanfang database. Study selection and data collection were conducted. Risks of bias were assessed by the Cochrane tool. Synthesis of results was done by RevMan 5.3. p<0.05 was considered significant difference. Subgroup analysis by classification of halitosis and sensitivity analysis were also conducted. Results . Seventeen studies were included. The follow-up length ranged from five days to eight weeks. CM had significantly better effect than WM on intraoral halitosis (I 2 =24%; RR=1.21 (95% CI, 1.04, 1.40), P=0.01) and extraoral halitosis (I 2 =0; RR=1.39 (95% CI, 1.19, 1.63), P<0.0001). CWM had significantly better effect than WM on intraoral halitosis (I 2 =0; RR=1.25 (95% CI, 1.16, 1.35), P<0.00001) and extraoral halitosis (I 2 =0; RR=1.19 (95% CI, 1.08, 1.31), P=0.0004). Subgroup analysis and sensitivity analysis showed insignificant results. Conclusion . With the limitation of our study, both CM and CWM have significantly better effect on halitosis than WM. More effort should be made to explore long-term effect of CM and CWM on halitosis. This study was registered with the PROSPERO (ID: CRD42018107229).